Study the Performance of Hybrid Constructed Wetland with Pumice Substrate and Vetiver Plants in Urban Wastewater Treatment - J. Abedi-Koupai; V. Arab-Nasrabadi; A. Sheykhan (علوم آب و خاک, 2022)
One of the ways to reduce the amount of wastewater pollution is the use of constructed wetlands. In this research, the performance of a hybrid constructed wetland with pumice ore and vetiver plant on urban wastewater has been investigated. Hybrid wetlands with these specifications were constructed in the vicinity of wastewater treatment at the Isfahan University of Technology. To evaluate the performance of constructed wetland the effects of three and six days of retention time on the removal efficiency were studied using a completely randomized design. On average, for three days of retention time, in the wetland with the vertical flow, the horizontal flow, and hybrid wetland, fecal coliform was 47.4, 98.3, and 99.1 percent, BOD5 was 7.6, 20.9, and 26.9 percent, and the COD was 4.6, 40.0, and 42.7 percent decreased, respectively. Also, during the six days of retention time in the wetland with the vertical flow, the horizontal flow, and hybrid wetland, fecal coliform was 61.6, 99.3, and 99.8 percent, BOD5 was 10.7, 29.9, and 37.4 percent, and COD was 16.0, 86.8, and 88.9 percent decreased, respectively. The combination of Pumice as a porous material with the ability to absorb the elements as well as vetiver as a plant capable of phytoremediation indicated a very suitable performance during low retention time.